FtsZ-Ring Regulation and Cell Division Are Mediated by Essential EzrA and Accessory Proteins ZapA and ZapJ in Streptococcus pneumoniae - Perez, Amilcar J.; Villicana, Jesus Bazan; Tsui, Ho-Ching T.; Danforth, Madeline L.; Benedet, Mattia; Massidda, Orietta; Winkler, Malcolm E. (Frontiers in Microbiology, 2021)
The bacterial FtsZ-ring initiates division by recruiting a large repertoire of proteins (the divisome; Z-ring) needed for septation and separation of cells. Although FtsZ is essential and its role as the main orchestrator of cell division is conserved in most eubacteria, the regulators of Z-ring presence and positioning are not universal. This study characterizes factors that regulate divisome presence and placement in the ovoid-shaped pathogen, Streptococcus pneumoniae (Spn), focusing on FtsZ, EzrA, SepF, ZapA, and ZapJ, which is reported here as a partner of ZapA. Epi-fluorescence microscopy (EFm) and high-resolution microscopy experiments showed that FtsZ and EzrA co-localize during the entire Spn cell cycle, whereas ZapA and ZapJ are late-arriving divisome proteins. Depletion and conditional mutants demonstrate that EzrA is essential in Spn and required for normal cell growth, size, shape homeostasis, and chromosome segregation. Moreover, EzrA(Spn) is required for midcell placement of FtsZ-rings and PG synthesis. Notably, overexpression of EzrA leads to the appearance of extra Z-rings in Spn. Together these observations support a role for EzrA as a positive regulator of FtsZ-ring formation in Spn. Conversely, FtsZ is required for EzrA recruitment to equatorial rings and for the organization of PG synthesis. In contrast to EzrA depletion, which causes a bacteriostatic phenotype in Spn, depletion of FtsZ results in enlarged spherical cells that are subject to LytA-dependent autolysis. Co-immunoprecipitation and bacterial two-hybrid assays show that EzrA(Spn) is in complexes with FtsZ, Z-ring regulators (FtsA, SepF, ZapA, MapZ), division proteins (FtsK, StkP), and proteins that mediate peptidoglycan synthesis (GpsB, aPBP1a), consistent with a role for EzrA at the interface of cell division and PG synthesis. In contrast to the essentiality of FtsZ and EzrA, ZapA and SepF have accessory roles in regulating pneumococcal physiology. We further show that ZapA interacts with a non-ZapB homolog, named here as ZapJ, which is conserved in Streptococcus species. The absence of the accessory proteins, ZapA, ZapJ, and SepF, exacerbates growth defects when EzrA is depleted or MapZ is deleted. Taken together, these results provide new information about the spatially and temporally distinct proteins that regulate FtsZ-ring organization and cell division in Spn.